(untitled) (Bangladesh Journal of Medical Science, 2025)
Temporomandibular joint disorders are one of the most common causes of orofacial pain that does not show any dental origin. These can lead to pain in the masticatory muscles and reduced mouth opening which can affect the daily life of an individual. The treatment includes both nonsurgical and surgical methods. When the nonsurgical method fails to treat the cause then the surgical method is prepared yet they lead to many risks. Thus a conservative approach to using a syringe was developed. There are two types: single-syringe technique and double- syringe technique. This article aims to review on the use of double-syringe technique, their advantages and limitations over the single syringe technique. BJMS, Volume: 24. Supplementary Issue 2025, Page : 63-65